Bistable dynamic coordination polymer showing reversible structural and functional transformations - Nagarkar, Sanjog S.; Das, Raja; Poddar, Pankaj; Ghosh, Sujit K. (Inorganic Chemistry, 2012)
A bistable dynamic coordination polymer [Ni(pca)(bdc)(0.5)(H2O)(2)] having a two-dimensional (2D) zigzag sheet structure is synthesized solvothermally. Topological analysis revealed that the frameworks have an hcb type of uninodal net. The compound exhibits guest specific reversible structural transformations accompanying reversible changes in physical properties driven by inherent flexibility and transformability.

Two-in-one: inherent anhydrous and water-assisted high proton conduction in a 3D metal-organic framework - Nagarkar, Sanjog S.; Unni, SreeKuttan M.; Sharma, Amitosh; Kurungot, Sreekumar; Ghosh, Sujit K. (Angewandte Chemie-International Edition, 2014)
The development of solid-state proton-conducting materials with high conductivity that operate under both anhydrous and humidified conditions is currently of great interest in fuel-cell technology. A 3Dmetal-organic framework (MOF) with acid-base pairs in its coordination space that efficiently conducts protons under both anhydrous and humid conditions has now been developed. The anhydrous proton conductivity for this MOF is among the highest values that have been reported for MOF materials, whereas its water-assisted proton conductivity is comparable to that of the organic polymer Nafion, which is currently used for practical applications. Unlike other MOFs, which conduct protons either under anhydrous or humid conditions, this compound should represent a considerable advance in the development of efficient solid-state proton-conducting materials that work under both anhydrous and humid conditions.
Keywords: conducting materials; fuel cells; metal-organic frameworks; porous materials; proton conduction

High hydroxide conductivity in a chemically stable crystalline metal-organic framework containing a water-hydroxide supramolecular chain - Nagarkar, Sanjog S.; Anothumakkool, Bihag; Desai, Aamod V.; Shirolkar, Mandar M.; Kurungot, Sreekumar; Ghosh, Sujit K. (Chemical Communications, 2016)
A chemically stable cationic MOF encapsulating an in situ formed water-hydroxide supramolecular anionic chain is realized for high hydroxide (OH-) ion conductivity in the solid-state (Type A). High OH- ion conductivity and low activation energy of the MOF demonstrate the advantage of the in situ incorporation of OH- ions to achieve efficient OH- ion conduction in the solid-state.